Procurando indicadores de educação inclusiva: as práticas dos professores de apoio educativo - Isabel Sanches; António Teodoro (Universidade do Minho, 2007)
Since the Declaration of Salamanca (1994) and related international political compromises, the inclusive school movement and therefore that of inclusive education is being overused by politians and education experts in their speeches. Special education, which works in parallel with the regular school system, should give way to inclusive education practices. These practices based on the human diversity and working with inclusive differentiation and cooperative learning methodologies can make the success of all through the success of each one and therefore lead to the emergence of a new school paradigm. In this paper, we look for signs of inclusive education in the support teachers practices. The research tool used was a questionnaire, which was applied to primary school teachers working in the Lisbon area. It was shown that the signs of inclusive education in the practices of the support teachers are scarce. Their pedagogical activity is closer to the Special Education methodologies. One wonders whether those responsible for the management of difference and diversity at school are indeed playing the role they are expected. If not, why not?